2009
DOI: 10.1097/opx.0b013e3181971985
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of the Effect of Contact Lens Wear on Self-Perception in Children

Abstract: Although contact lens wear does not affect global self-perceptions of 8- to 11-year-old myopic children their physical appearance, athletic competence, and social acceptance self-perceptions are likely to improve with contact lens wear. Eye care practitioners should consider the social and visual benefits of contact lens wear when choosing the most appropriate vision correction modality for children as young as 8 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 37 publications
4
55
1
Order By: Relevance
“…Physical differences from others may affect peer appraisals and/or children may think that peer appraisals are influenced by their glasses (called ''meta-stereotypes''; Vorauer, Hunter, Main, & Roy, 2000). Four studies have directly assessed the association between eyeglasses and children's self-concept (Dias, Hyman, Manny, & Fern, 2005;Lyon, Rainey, & Bullock, 2002;Terry, Soni, & Honer, 1997;Walline et al, 2009), baseline results of two were reported in previous publications (Dias, Manny, Hyman, & Fern, 2002;Walline et al, 2006;Walline, Jones, & Prinstein, 2005). Lyon and colleagues (2002) studied self-concepts reported by children aged eight to fourteen and found no evidence that having eyeglasses affects the global self-concept of children, although this study lacked statistical power.…”
Section: Effect Of Glasses On the Children Who Wear Themmentioning
confidence: 89%
See 1 more Smart Citation
“…Physical differences from others may affect peer appraisals and/or children may think that peer appraisals are influenced by their glasses (called ''meta-stereotypes''; Vorauer, Hunter, Main, & Roy, 2000). Four studies have directly assessed the association between eyeglasses and children's self-concept (Dias, Hyman, Manny, & Fern, 2005;Lyon, Rainey, & Bullock, 2002;Terry, Soni, & Honer, 1997;Walline et al, 2009), baseline results of two were reported in previous publications (Dias, Manny, Hyman, & Fern, 2002;Walline et al, 2006;Walline, Jones, & Prinstein, 2005). Lyon and colleagues (2002) studied self-concepts reported by children aged eight to fourteen and found no evidence that having eyeglasses affects the global self-concept of children, although this study lacked statistical power.…”
Section: Effect Of Glasses On the Children Who Wear Themmentioning
confidence: 89%
“…Lyon and colleagues compared children with and without glasses on several dimensions of the self-concept-finding no negative, perhaps even a positive effect of glasses-but, given their small sample of children with glasses, it is difficult to make conclusions. A larger, recent study (Walline et al, 2009) addressed self-esteem in 8-to 11-year-olds who received contact lenses or continued to wear glasses (Walline et al, 2007). Over a three-year period, children's global self-esteem did not differ, but children who wore contact lenses showed a relatively more positive development in their self-perceptions of physical appearance and athletic competence.…”
Section: Effect Of Glasses On the Children Who Wear Themmentioning
confidence: 95%
“…Other studies found that 86% to 91% of children continue to wear soft contact lenses for three years. 17, 18 Therefore, both short-term and long-term adaptation rates are better for soft contact lenses than for GP contact lenses, although this study demonstrates that children can successfully adapt to and maintain GP lens wear.…”
Section: Discussionmentioning
confidence: 77%
“…15 Older children may elect to wear contact lenses for refractive error correction because they do not like their appearance with glasses or because their glasses are uncomfortable. 4, 5, 17, 18 Children are capable of wearing gas permeable (GP) contact lenses, 3, 4, 6–9 soft contact lenses (SCL), 2, 17 and corneal reshaping contact lenses. 1, 19–21 They are also capable of complying with a contact lens care regimen.…”
mentioning
confidence: 99%
“…Ten percent loss to follow-up was conservatively determined based on previous retention rates of 96.5% 42 and 100% 43 in previous 3-year longitudinal contact lens studies conducted on children of similar ages by members of the study team.…”
Section: Methodsmentioning
confidence: 99%